miRNA-Dependent Control of Homeostatic Plasticity in Neurons - Dubes, Sandra; Favereaux, Alexandre; Thoumine, Olivier; Letellier, Mathieu (Frontiers in Cellular Neuroscience, 2019)
Homeostatic plasticity is a form of plasticity where neurons compensate for changes in neuronal activity through the control of key physiological parameters such as the number and the strength of their synaptic inputs and intrinsic excitability. Recent studies revealed that miRNAs, which are small non-coding RNAs repressing mRNA translation, participate in this process by controlling the translation of multiple effectors such as glutamate transporters, receptors, signaling molecules and voltage-gated ion channels. In this review, we present and discuss the role of miRNAs in both cell-wide and compartmentalized forms of homeostatic plasticity as well as their implication in pathological processes associated with homeostatic failure.